2015
DOI: 10.1002/adfm.201503613
|View full text |Cite
|
Sign up to set email alerts
|

Iron–Nitrogen‐Doped Vertically Aligned Carbon Nanotube Electrocatalyst for the Oxygen Reduction Reaction

Abstract: A highly active iron-nitrogen-doped carbon nanotube catalyst for the oxygen reduction reaction (ORR) is produced by employing vertically aligned carbon nanotubes (VA-CNT) with a high specifi c surface area and iron(II) phthalocyanine (FePc) molecules. Pyrolyzing the composite easily transforms the adsorbed FePc molecules into a large number of iron coordinated nitrogen functionalized nanographene (Fe-N-C) structures, which serve as ORR active sites on the individual VA-CNT surfaces. The catalyst exhibits a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
157
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 42 publications
3
157
0
Order By: Relevance
“…To the best of our knowledge, our CNT@Fe-N-PC catalyst showed the best ORR performance in an acidic medium compared with all previously reported Fe-N-C and other non-noble-metal catalysts (Supplementary Table 2). 11,12,13,20,22,27,28,31,[37][38][39][40] In addition to the high activity, we further studied the durability of the CNT@Fe-N-PC catalyst. Figure 3c shows that the current density decay is 12% after 40 000 s of testing, much smaller than that (57%) of commercial Pt/C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our CNT@Fe-N-PC catalyst showed the best ORR performance in an acidic medium compared with all previously reported Fe-N-C and other non-noble-metal catalysts (Supplementary Table 2). 11,12,13,20,22,27,28,31,[37][38][39][40] In addition to the high activity, we further studied the durability of the CNT@Fe-N-PC catalyst. Figure 3c shows that the current density decay is 12% after 40 000 s of testing, much smaller than that (57%) of commercial Pt/C.…”
Section: Resultsmentioning
confidence: 99%
“…Notable progress has been made in recent years in the development of low-cost noble-metal-free catalysts, including heteroatom-doped carbon materials, 4-6 Fe 3 C-based materials [7][8][9] and transition-metalcoordinated nitrogen-doped carbon catalysts (Me-N-C, Me: Fe and/ or Co). [10][11][12] Although these materials demonstrate desirable ORR catalytic activity comparable to that of Pt/C in an alkaline medium, only Me-N-C catalysts, particularly Fe-N-C, show relatively good catalytic activity and durability in acidic conditions, [13][14][15] which makes them attractive for use in proton exchange membrane fuel cells. Fe-N-C catalysts are generally synthesized by pyrolyzing precursors containing carbon, nitrogen, and iron at temperatures above 700°C, to achieve high activity and a robust structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2b-d display the high resolution N 1s spectra of the three Fe-NS/PC catalysts. All the spectra can be deconvoluted into four peaks corresponding to pyridinic N (N1, 398.1-398.7 eV), pyrrolic N (N2, 399.78-400.7 eV), graphitic N (N3, 400.99-401.3 eV), and oxidized N (N4, 402-404.27 eV) [25,26], respectively. Previous reports have demonstrated that both pyridinic N and graphitic N may participate the oxygen reduction reaction [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Moreover, for tuning the coordination of Fe atoms, the traditional methods mainly focus on introducing the reacting gas atmosphere (e.g., NH 3 ) during the pyrolysis treatment, or adding extra ligand species (e.g., pyridine and imidazole) for Fe atoms. [21,24,31] Nevertheless, it still remains a large challenge to prepare single-atomic Fe catalysts by a facial and effective method for their commercial and technological feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…[15,[21][22][23] Although the original Fe-N 4 moieties (e.g., the central part of iron phthalocyanine) have been proven to be the highly active sites for ORR, the coordination environment of Fe still needs to be optimized. [24,25] Considering that the high-temperature heat-treatment may make the Fe atoms aggregate and break the N-contained functional groups, [26] choosing an appropriate support material or tuning the coordination environment for Fe may be the important step to prepare high-performance SACs of Fe.…”
Section: Introductionmentioning
confidence: 99%